2017
DOI: 10.5194/hess-21-1669-2017
|View full text |Cite
|
Sign up to set email alerts
|

Identification of dominant hydrogeochemical processes for groundwaters in the Algerian Sahara supported by inverse modeling of chemical and isotopic data

Abstract: Abstract. Unpublished chemical and isotopic data taken in November 1992 from the three major Saharan aquifers, namely the Continental Intercalaire (CI), the Complexe Terminal (CT) and the phreatic aquifer (Phr), were integrated with original samples in order to chemically and isotopically characterize the largest Saharan aquifer system and investigate the processes through which groundwaters acquire their mineralization. Instead of classical Debye-Hückel extended law, a specific interaction theory (SIT) model,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The Continental Terminal, a continental formation composed primarily of sands deposited and solidified in The hydrographic network of the Ouargla basin is sparse and consists of a fossil wadi called Wadi Mya and two functional wadis called Wadi N'sa and Wadi M'zab. All these wadis have a temporary flow (Slimani et al 2017).…”
Section: Presentation Of the Study Areamentioning
confidence: 99%
“…The Continental Terminal, a continental formation composed primarily of sands deposited and solidified in The hydrographic network of the Ouargla basin is sparse and consists of a fossil wadi called Wadi Mya and two functional wadis called Wadi N'sa and Wadi M'zab. All these wadis have a temporary flow (Slimani et al 2017).…”
Section: Presentation Of the Study Areamentioning
confidence: 99%
“…In an effort to evaluate the situation, very few studies have been conducted to assess the physicochemical quality of the phreatic aquifer for drinking and irrigation use, and the impact of direct discharge of wastewater and drainage waters into the phreatic aquifer of Oued Souf, as well as its influence on the degradation of the phreatic groundwater quality using hydrogeochemical, geographic information system (GIS), and isotopic ap-proaches [30][31][32][33][34]. No study has been conducted to assess heavy-metal contamination in the phreatic groundwater aquifer under its illegal utilization for irrigation and industry.…”
Section: Introductionmentioning
confidence: 99%
“…Northern Sahara of Algeria has been the subject of research in several studies, that have mainly highlighted on the geological and hydrogeological contexts of their aquifers, in reconnaissance of the northern Sahara aquifer system [7][8][9][10][11][12][13]. In addition to geological and hydrogeological studies, various studies undertaken over the past thirty plus years have shown that the groundwater's quality of this region is characterized by excessive total mineralization, most often associated with high hardness and high fluoride concentrations, which often exceed the guide values recommended by the World Health Organization (WHO) and values of Algerian limits using conventional methods hydro-chemically, statistically, and even using isotopic methods [14][15][16][17][18][19][20][21][22][23]. Other studies focused on the treatment of these groundwaters using different techniques, such as lime precipitation and electrocoagulation using bipolar aluminum electrodes and activated natural materials [24][25][26].…”
Section: Introductionmentioning
confidence: 99%